1993
DOI: 10.1177/070674379303800401
|View full text |Cite
|
Sign up to set email alerts
|

Misidentification Delusions, Facial Misrecognition, and Right Brain Injury

Abstract: Individuals suffering from misidentification syndromes may present with right hemispheric pathology and deficits in facial recognition. In addition, misidentification delusions have been associated with aggressive behaviour. The possible linkage between misidentification phenomena, facial recognition, and aggression is discussed, illustrated by the case of a patient suffering from an organic delusional disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…The current consensus in regard to Capgras delusion is that the disorder is at least partially organic in origin. A number of case studies of Capgras patients have revealed right hemisphere lesions as well as bifrontal and bitemporal lesions (Alexander et aL, 1979;Stuss, 1990, Crichton andLewis, 1990;Cutting, 1991;Silva et aL, 1993;Stuss and Benson, 1986;.…”
Section: Are Both Left and Right Hemisphere Mechanisms Necessary For mentioning
confidence: 99%
See 2 more Smart Citations
“…The current consensus in regard to Capgras delusion is that the disorder is at least partially organic in origin. A number of case studies of Capgras patients have revealed right hemisphere lesions as well as bifrontal and bitemporal lesions (Alexander et aL, 1979;Stuss, 1990, Crichton andLewis, 1990;Cutting, 1991;Silva et aL, 1993;Stuss and Benson, 1986;.…”
Section: Are Both Left and Right Hemisphere Mechanisms Necessary For mentioning
confidence: 99%
“…Returning now to hemispheric studies related to Capgras delusion, there is considerable evidence which points to the possibility of right hemisphere involvement (Alexander et al, 1979;Benson and Stuss, 1990;Crichton and Lewis, 1990;Cutting, 1991;Silva et aL, 1993;Stuss and Benson, 1984; in Capgras dehlsion. Using computerized tomography, Alexander et aL (1979) were the first researchers to report a case of Capgras delusion clearly related to a specific neurologic lesion in the right hemisphere with predominantly frontal and temporal lobe damage.…”
Section: Hemispheric Studies Related To Capgras Delusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in a recent communication Silva et al [30] gave an account of a 55-year-old man who had been shot in the head by a robber and developed left-sided hemiplegia: he displayed difficulties in recognising faces, some of which could appear distorted; he then showed symptoms of CD for his wife and became aggressive, threatening to kill her. Neuro 182 Ellis Right Hemisphere and CD imaging revealed brain loss of the right frontal lobe and right lateral ventricular enlargement.…”
Section: Studymentioning
confidence: 99%
“…37 DMS generally and Capgras specifically have also been seen with right-hemisphere temporal and tempoparietal strokes 38,39 and in right-hemisphere traumatic brain injury. 40 One of the first large comparisons of primary psychiatric versus neurological DMS, which was published in 1993, 41 found some tendency toward delusions of place in dementia and delusions of person in psychiatric disorders, but with a similarity in both conditions in that the delusional content centered on objects of personal significance to the patient. Not surprisingly, the background histories were different, with psychiatric patients having had other paranoid symptoms before the onset of misidentification, and dementia patients often presenting with an initial psychosis involving misidentification.…”
Section: Commentary By David a Kahn MDmentioning
confidence: 99%